Application of Discovery Learning Method in Mathematical Proof of Students in Trigonometry - Hadi, Windia; Faradillah, Ayu (Desimal: Jurnal Matematika, 2020)
Trigonometry is a part of mathematics in learning that is related to angles. The purpose of this study was to determine the effect of the application of discovery learning methods in students' mathematical proof ability on trigonometry. The research method used in this study is quasi-experimental. The population in this study was the second semester of 2016/2017. The sample was 66 people who were determined by purposive sampling. The instrument used in this study was a mathematically proof ability test. Analysis of the data used is the t-test. The results of this study are (1) based on an average score of mathematical proof ability The student's mathematical proof ability in applying the Discovery Learning Method to trigonometry is not higher than the mathematical proof ability of students who do not use the discovery method (2) there is no significant influence in the application of learning methods Discovery in students' mathematical proofs on trigonometry.